Analysis of Constituents for Phenotyping Drought Tolerance in Crop Improvement - Setter, Tim L. (Frontiers in Physiology, 2012)
Investigators now have a wide range of analytical tools to use in measuring metabolites, proteins and transcripts in plant tissues. These tools have the potential to assist genetic studies that seek to phenotype genetic lines for heritable traits that contribute to drought tolerance. To be useful for crop breeding, hundreds or thousands of genetic lines must be assessed. This review considers the utility of assaying certain constituents with roles in drought tolerance for phenotyping genotypes. Abscisic acid (ABA), organic and inorganic osmolytes, compatible solutes, and LEA proteins, are considered. Confounding effects that require appropriate tissue and timing specificity, and the need for high throughput and analytical cost efficiency are discussed. With future advances in analytical methods and the value of analyzing constituents that provide information on the underlying mechanisms of drought tolerance, these approaches are expected to contribute to development crops with improved drought tolerance.